What do you think of transparent pay? The reflexive thematic analysis of opinions about pay transparency in Poland - Konrad Kulikowski (Central European Management Journal)
Purpose – With pay transparency (PT) as an emerging trend in organizations around the world and the European Union promoting open pay regulations, PT is of increasing interest to scientists, managers and policymakers. However, it is still unclear what people think about PT and what theoretical perspectives might explain people's views on transparent pay. Therefore, the purpose of this paper is to explore and systematize opinions about PT and to propose theoretical frameworks to understand different reactions to it. Design/methodology/approach – Qualitative reflexive thematic analysis of the Internet debate that emerged in Poland in 2019 in response to the proposition of new law regulations aimed to improve PT by introducing obligatory pay ranges in job offers. Findings – The author's analysis revealed a set of 41 specific and often opposite opinions about PT, which allow for the systematization of hopes and concerns related to PT around the 7 favorable and 6 unfavorable higher-order themes. Social implications – The author's results might inform policymakers and managers about the possible risks and benefits of PT implementation. Revealed opposite opinions about PT raise awareness that PT policies, while solving some social problems, might simultaneously create others. Originality/value – The author provides new insights into opinions that people hold about transparent pay based on real-world data. The author suggests theoretical perspectives for understanding and predicting reactions to PT, such as Hobfoll's Conservation of Resources Theory and Adam`s Equity Theory. Based on this, the authors propose that opposite opinions about PT might be explained by (a) perceived pay dispersion fairness and (b) perceived PT costs-benefits ratio.